The level of Internet Financial Reporting Disclosure in listed companies in Sri Lanka - Krishnasamy, T.; Pratheepkanth, P. (University of Jaffna, 2020)
This study aims to analyze what extent Internet Financial Reporting (IFR) disclosure in the Sri Lankan Context by using the secondary data collected from the 50 sample company’s websites. Descriptive statistics related to IFR-Index and the one-sample t- test is used to ascertain the current IFR disclosure level in Sri Lanka for the financial years 31st March 2020. The results indicate that the overall level of IFR-Index is only 42%. The total content index sub-score is, on average, 41%, and the level of presentation format index sub-score on average is 44%. The study relied upon that the level of IFR practices in the Sri Lankan context is very poor compared with counterparts. This study implies the Sri Lankan companies and policymakers have to take action to promote such reporting practices in Sri Lanka.
Keywords: Colombo Stock Exchange (CSE); content attributes; internet financial reporting; presentation attributes